Trends in private sector development in World Bank education projects - Sosale, Shobhana, 1963- 1963- (Policy research working paper, 2000)
The principle underlying trends in Bank education projects is that strengthening the private sector's role in noncompulsory education over time will release public resources for the compulsory (primary) level. The public and private sectors have complementary roles to play